Study of histopathological findings of endometrial biopsy in women with abnormal uterine bleeding - Sanjita; Ismat Khanam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Abnormal uterine bleeding is one of the most common problems presenting in OPD to the gynecologist regardless of the age of the women. The main aim was to study the frequency of different histopathological findings of endometrial sample in patients with abnormal uterine bleeding. Methods: This study was conducted on 82 patients from December 2021 to November 2022 in the department of obstetrics and gynecology. Patients with AUB due to gestational cause like missed abortion, incomplete abortion, retained products of conception and with uterine fibroid were excluded from study. Results: Abnormal uterine bleeding (AUB) presented mostly in the 41-50 years of age. The commonest histopathological pattern in abnormal uterine bleeding was normal physiological changes of menstrual cycles secretory phase (29%). Endometrial hyperplasia was the most common endometrial pathology observed in 11% patients. Conclusions: Endometrial evaluation in abnormal uterine bleeding helps in early detection of pre-neoplastic conditions and malignancy to provide early treatment and avoid further complications.